Scrotal sac leiomyoma: Case report of a rare benign scrotal mass - Titilope Aluko, BS; Zachary Masi, MD; Jeffrey Tomaszewski, MD; Pauline Germaine, DO (Radiology Case Reports, 2018)
Leiomyomas are benign mesenchymal tumors, the overwhelming majority of which are located in the uterus. Rare cases arise in other organs, including the scrotum, pelvis, bladder, and spermatic cord. This report evaluates the case of a 37-year-old man with a history of prior left inguinal hernia repair, who presented with a painless right scrotal mass. He first noticed the mass approximately 1 year prior to his initial visit. Subsequent ultrasound of the scrotum demonstrated a 5-cm circumscribed, hypoechoic, mildly vascular extratesticular mass located within the right hemiscrotum. Based on the initial imaging, the differential diagnosis included lipoma, adenomatoid tumor, papillary cystadenoma, leiomyoma, fibrous pseudotumor, sarcoid granuloma, sarcoma (including liposarcoma, rhabdosarcoma, or leiomyosarcoma), lymphoma, and an extranumerary testis. The mass had circumscribed margins, suggesting an encapsulated lesion, and was completely separate from the testicle on ultrasound. Despite this, testicular malignancy was not entirely excluded as a diagnosis, although it was considered far less likely. The patient was definitively treated with surgical excision of the mass. Pathology of the surgical specimen confirmed diagnosis of leiomyoma, a rare scrotal mass. Keywords: Extratesticular mass, Leiomyoma, Leiomyoma of scrotum